(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Burn injury and wound is a pig problem that assists the pathogens to grow and cause infection. 149 burninjury swabs were taken from different site of the patients’ body ages (11-53 years old). All samples weretested to isolate the sigificant microorganisms that found in burn injury. Antibiotics test was performed byusing disc diffusion way that stated by Kirby-Baucer. Results appeared that the most frequent pathogen inburn injury was Pseudomonas aeruginosa 33(22.14%) and followed by E.coli 31(20.8%), Staphylococcusaureus 28(18.79%), Proteus vulgaris 26(17.48%), Coagulase-negative Staphylococci 12(8.05%), Proteusmirabilis 10(6.71%), Klebsiella pneumonia 5(3.35%) and Candida spp. 4(2.68%) respectively. Antibiotictest showed that Staphylococcus aureus was a high resistance against Gentamycin and ciprofloxacin, butit was sensitive to Vancomycin and Imipenem. Coagulase negative Staphylococci showed a resistanceto Gentamicin, Ciprofloxacin and Ceftazidime, but it was sensitive to Amikacin, Oxacillin, Cefotaxim,Vancomycin, Imipenem and Cefepime. P. aeruginosa showed resistance against Cefotaxime, Aztreonam,Gentamicin and Ceftazidime. Whlist it showed a high sensitivity against Imipenem, Cefepime andTobramycin. E.coli showed a high resistance against Ceftriaxone, Ciprofloxacin and Cephalothin. whilstit showed a high sensitivity against Ticarcillin/clavulanic acid, Imipenem, Cefepime and Tobramycin.Proteus vulgaris showed a high resistance against Ceftriaxone, Ceftazidime, Amikacin, Cephalothin andGentamicin. Whilst it showed a high sensitivity against Cefotaxime, Aztreonam, Ticarcillin/clavulanicacid and Imipenem. Proteus mirabilis showed resistance against Amikacin, Ciprofloxacin, Ceftriaxone,Gentamicin and Cephalothin. Whilst it showed a high sensitivity against Ceftazidime, Cefotaxime,Aztreonam, Ticarcillin/clavulanic acid, Imipenem, Cefepime and Tobramycin. Klebsiella pneumoniashowed resistance against Ciprofloxacin, Ceftazidime, Cefotaxime and Aztreonam. whilst it showed a highsensitivity against Ceftriaxone, Amikacin, Gentamicin, Cephalothin, Ticarcillin/clavulanic acid, Imipenem,Cefepime and Tobramycin. The current study was aimed to determine the most frequent pathogens in burninjury and test their antibiotics susceptibility in hospitalize patients in Najaf city.